2005
DOI: 10.1128/mcb.25.8.3261-3275.2005
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte Enhancer Factor 2 Activates Promoter Sequences of the Human AβH-J-J Locus, Encoding Aspartyl-β-Hydroxylase, Junctin, and Junctate

Abstract: Alternative splicing of the locus A␤H-J-J generates three functionally distinct proteins: an enzyme, A␤H (aspartyl-␤-hydroxylase), a structural protein of the sarcoplasmic reticulum membrane (junctin), and an integral membrane calcium binding protein (junctate). Junctin and junctate are two important proteins involved in calcium regulation in eukaryotic cells. To understand the regulation of these two proteins, we identified and functionally characterized one of the two promoter sequences of the A␤H-J-J locus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 77 publications
3
39
0
Order By: Relevance
“…2B). In contrast, we have previously shown that the expression directed by the P2 promoter is tissue specific, as a high level of transcription is present, in particular, in skeletal muscle, cardiac muscle, and brain [2,13]. The P1 promoter directs transcription also in RD, HepG2, human breast cancer (MCF7), human cervix epithelial carcinoma (HeLa) and human embryonic kidney (Hek293) tumor cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2B). In contrast, we have previously shown that the expression directed by the P2 promoter is tissue specific, as a high level of transcription is present, in particular, in skeletal muscle, cardiac muscle, and brain [2,13]. The P1 promoter directs transcription also in RD, HepG2, human breast cancer (MCF7), human cervix epithelial carcinoma (HeLa) and human embryonic kidney (Hek293) tumor cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(C) AβH‐J‐J P1 and P2 promoter activity in the RD cell line. Cells were transiently transfected with the reporter constructs that present the maximal transcriptional activity of each promoter [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations